2005
DOI: 10.1111/j.1095-8312.2005.00457.x
|View full text |Cite
|
Sign up to set email alerts
|

Inferences of selection and migration in the Danish house mouse hybrid zone

Abstract: We analysed the patterns of allele frequency change for ten diagnostic autosomal allozyme loci in the hybrid zone between the house mouse subspecies Mus musculus domesticus and M. m. musculus in central Jutland. After determining the general orientation of the clines of allele frequencies, we analysed the cline shapes along the direction of maximum gradient. Eight of the ten clines are best described by steep central steps with coincident positions and an average width of 8.9 km (support limits 7.6-12.4) flank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
152
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(165 citation statements)
references
References 64 publications
12
152
1
Order By: Relevance
“…In three of these, introgression of domesticus mtDNA was found in musculus populations, and in two, introgression of musculus mtDNA was found in domesticus populations (Božíková et al, 2005 and references therein). A study of ten allozyme loci showed asymmetry always in the direction of domesticus into musculus (Raufaste et al, 2005). Several studies have found that musculus females prefer musculus males, but domesticus females display no breeding preference (Smadja and Ganem, 2002;Smadja et al, 2004;Bimova et al, 2005;Ganem et al, 2005).…”
Section: Rja Buggsmentioning
confidence: 98%
“…In three of these, introgression of domesticus mtDNA was found in musculus populations, and in two, introgression of musculus mtDNA was found in domesticus populations (Božíková et al, 2005 and references therein). A study of ten allozyme loci showed asymmetry always in the direction of domesticus into musculus (Raufaste et al, 2005). Several studies have found that musculus females prefer musculus males, but domesticus females display no breeding preference (Smadja and Ganem, 2002;Smadja et al, 2004;Bimova et al, 2005;Ganem et al, 2005).…”
Section: Rja Buggsmentioning
confidence: 98%
“…Studies include work on taxa with male heterogamety, where maternally inherited loci are seen to introgress further than autosomal and paternally inherited loci (for example, in the Mus musculus-M. domesticus hybrid zone, mitochondrial DNA introgresses to a greater degree than autosomal loci (Raufaste et al, 2005)), as well as taxa with female heterogamety (where biparentally inherited loci are seen to introgress deeper than maternally inherited ones; Jiggins et al, 1997;Helbig et al, 2001;Cianchi et al, 2003;Kronforst et al, 2006). As a particularly comprehensive example, Carling and Brumfield (2008) studied cline width in a (female-heterogametic) avian hybrid zone and found that Z-linked and mitochondrial genes introgressed less deeply than autosomal markers, which is consistent with HR.…”
Section: Schilthuizen Et Almentioning
confidence: 99%
“…Furthermore, a balance between gene flow and selection against hybrids often leads to the formation of narrow hybrid zones, reducing recombination and therefore allowing divergence between populations either side of the zone to continue (parapatric speciation; Kondrashov, 2003). Clines of sex-linked loci are often narrower than those of autosomal loci, for example in the house mouse (Tucker et al, 1992;Dod et al, 1993Dod et al, , 2005Raufaste et al, 2005;Macholán et al, 2007), indicating either that selection against hybrids is more efficient on the X/Z chromosome or that it is more likely to contain genes selected against in hybrids. Either way, recombination in parapatry is lower for X/Z-linked loci than autosomal loci, increasing their potential for divergence.…”
Section: Evolution Of Genetic Incompatibilitymentioning
confidence: 99%